Train teachers to transform the didactic practices. A case study - Pentucci, Maila (Form@re - Open Journal per la formazione in rete, 2016)
What device for in-service teacher training could significantly and deeply change the didactic practices and their underlying conceptualization? The issue presents a longitudinal case study, made by a team of researchers with a primary school teacher, according to the Recherche Collaborative, Analyse Plurielle and Analyse de Pratique fundamentals (Lenoir, 2012; Vinatier & Altet, 2008). The research shows the transformations emerged both at the level of the transposition and didactic design, both at the level of destructuring and restructuring patterns of action.The recursive co-analysis of didactic action, systematized by a detailed protocol to collect and to investigate the data, allowed the teacher to take a reflective attitude. Following this, she has been able to incorporate, into her professional profile, the reflection on the action. She has put into practice a real type of transformative learning. Formare gli insegnanti per trasformare le pratiche didattiche. Uno studio di caso Quale dispositivo per la formazione in servizio degli insegnanti potrebbe contribuire ad un cambiamento significativo e profondo nelle pratiche didattiche e nelle concettualizzazioni ad esse sottese? L’articolo presenta un caso di studio longitudinale, condotto da un team di ricercatrici con un’insegnante di scuola primaria, secondo i principi della Ricerca Collaborativa (Lenoir, 2012) e dell’Analisi Plurale delle pratiche (Vinatier & Altet, 2008) che mostra i processi di trasformazione emersi sia a livello di trasposizione didattica e di progettazione, sia a livello di destrutturazione e ristrutturazione degli schemi d’azione propri del soggetto. La co-analisi ricorsiva dell’azione, sistematizzata da un protocollo articolato di raccolta e indagine sui dati, ha permesso all’insegnante di assumere una postura riflessiva che le ha consentito di incorporare la riflessione sull’azione nel suo profilo professionale, mettendo in atto un tipo di apprendimento realmente trasformativo.